Apoptosis of keratinocytes and serum DNase I activity in patients with cutaneous lupus erythematosus: relationship with clinical and immunoserological parameters. (30th September 2016) - Skiljevic, D.; Bonaci‐Nikolic, B.; Brasanac, D.; Nikolic, M.
Abstract: Background: Dysregulation of apoptosis has an important role in the induction of autoimmunity. Objective: To evaluate the influence of keratinocyte apoptosis and deoxyribonuclease I (DNase I) activity on the clinical and immunoserological parameters of cutaneous lupus erythematosus (CLE). Methods: We studied 69 CLE patients (39 with discoid LE (DLE), 12 with subacute CLE (SCLE), 12 with acute and 6 with intermittent CLE). Thirty of sixty‐nine patients fulfilled criteria for systemic LE (SLE). Apoptotic index (AI) was evaluated immunohistochemically in lesional and non‐lesional, photoprotected skin. Serum DNase I activity, antichromatin and anti‐ENA antibodies were measured by ELISA. Disease activity was determined by SLEDAI‐2K, SLICC/ACR, CLASI and RCLASI. Results: AI in lesions was higher than in non‐lesional skin ( P < 0.001). There was no difference in AI between CLE and SLE patients. Patients with SCLE had higher lesional AI than patients with DLE ( P < 0.05). We found a positive correlation between the lesional AI with CLASI A ( P < 0.05) and RCLASI D ( P < 0.05). CLE and SLE patients had significantly lower DNase I activity than healthy controls ( P < 0.001). Patients with normal DNase I activity and low AI had significantly lower CLASI A than patients with decreased DNase I activity and/or elevated AI ( P < 0.05). Conclusions: Increased keratinocyte apoptosis characterizes lesions of all CLE forms, especially of SCLE. AI correlates with CLE markers of acute and chronic inflammation. Normal level of apoptosis and DNase I activity simultaneously reduce the level of acute inflammation in CLE. Serum DNase I activity and AI might be important biomarkers in the evaluation of CLE patients.